2013
DOI: 10.1111/ane.12112
|View full text |Cite
|
Sign up to set email alerts
|

Time course of NT-proBNP levels after acute ischemic stroke

Abstract: NT-proBNP levels were highest in the first 2 days after ischemic stroke and declined significantly thereafter. However, the area under the curve for the three time points was similar. The first 72 hours after ischemic stroke have a similar diagnostic accuracy to diagnose cardioembolic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Because of unavailability of the requested data or lack of response from authors, we finally selected 23 articles (Figure 1). [16][17][18][19][20][21][22][23][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The median quality score was 9 (minimum=5 and maximum=11; data not shown). These 23 included articles corresponded to 18 different cohorts of patients, 16 of which had data from patients with a defined cause (cardioembolic, LAA, or SVD) and 2 cohorts containing data of undetermined patients only.…”
Section: Resultsmentioning
confidence: 93%
“…Because of unavailability of the requested data or lack of response from authors, we finally selected 23 articles (Figure 1). [16][17][18][19][20][21][22][23][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The median quality score was 9 (minimum=5 and maximum=11; data not shown). These 23 included articles corresponded to 18 different cohorts of patients, 16 of which had data from patients with a defined cause (cardioembolic, LAA, or SVD) and 2 cohorts containing data of undetermined patients only.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, an alternative explanation would be a higher influence of stroke on NT‐proBNP concentration in comparison to BNP. Both biomarkers are increased after stroke [24,25] and the infarcted area in the brain may be a potential source of their expression [26]. As NT‐proBNP has a longer half‐life, the confounding effects of stroke may last longer, even until 72 h after stroke onset [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although the great majority of the samples were obtained in the first 24 h after the TIA, in some cases they were not extracted until 48 or 72 h after the event. In any case, previous studies indicate that the highest values of serum NT-pro-BNP are found during the first 3 days after the stroke and that the usefulness of the determinations is similar within that time interval [34].…”
Section: Limitationsmentioning
confidence: 71%